منهجية التفسير الموضوعي عند محمد محمود حجازي ومحمد باقر الصدر : دراسة تحليلية مقارنة - مكرم الله، طارق طه (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
Shaikh Muḥammad Maḥmud Ḥijazi and Sayyid Muḥammad Baqir al-Ṣadr were among the most prominent scholars who have contributed significantly to the scientific debate in the area of thematic interpretation. This research is an attempt to study and analyse methodology employed by al-Ṣadr and Ḥijazi in their approach towards thematic interpretation at both theoretical and practical levels. Throughout this study, the researcher has relied on the inductive approach by gathering the opinions and concepts expressed by both Ḥijazi and al-Ṣadr on thematic interpretations. The study was done through their prominent works within the area namely; al-Wiḥdat al-Mawḍu'iyyah fī al-Qur'an al-Karīm by Ḥijazi and al-Tafsīr al-Mawḍu'iy wa al-Filsafat al-Ijtima'iyyah fī al-Madrasat al-Qur'aniyyah by al-Ṣadr. Following the collection and gathering of views, the researcher adopted an analytical method by analysing the texts and opinions of each of scholar on thematic interpretation. The researcher then employed comparative analysis between the views of the two and their approach towards thematic interpretation in terms of theory, methodology and practice. This step is necessary in order to highlight the points of agreements and disagreements between them, and to reveal the complementarity dimension between their approaches. This research reveals an important aspect of contribution by both Ḥijazi and al-Ṣadr in discovering proper methods of approaching the Qur'anic discourse, simultaneously keeping abreast of recent developments on issues pertaining to the Muslims' life. It also provides a systematic lesson for researchers and interpreters on how to deal with Qur'anic text and to clarify the theories and rules of the Qur'an in various matters of thought and life.